Statistical Analysis: Marine Capture Production of West Bengal, Andhra Pradesh and Kerala - Rajani, M.; Balasubramanian, A. (International Journal of Bio-resource and Stress Management, 2021)
In this study, basic statistical tools viz., measure of central tendency, dispersion, skewness, correlation and ANOVA tests were applied to analyze the marine capture production data of different groups like Pelagic, Demersal, Crustaceans and Molluscs collected from Marine Products Exports Development Authority, Cochin for the period from 1985 to 2011 pertaining to three costal states of India such as West Bengal, Andhra Pradesh and Kerala. Each group of fish was considered as a treatment for the chosen time series period. Descriptive statistics revealed the elevation of production levels of different groups for states studied. Molluscs production from Andhra Pradesh did not vary much between the years having low standard deviation (918.46) while pelagic fish production varied highly in Kerala having standard deviation (86818.71). In the case of crustaceans, West Bengal had high coefficient of variance (100) and Kerala had low coefficient of variance (19.50) for demersal group. Various kinds of skewed distribution could be observed between groups in all three states. Marine fish productions of different groups from the states of West Bengal and Andhra Pradesh had good correlation except with Kerala where even negative production was observed especially in crustacean production. ANOVA also endorsed that significant production level among various fish groups could be observed in all the states. Similarly, the fish production of every group obtained from the states of West Bengal and Andhra Pradesh differed significantly with Kerala despite no difference in various fish production between the states of West Bengal and Andhra Pradesh could be found.